Mount Ararat and Noah’s Ark History, Myth and Land - Belli, Vedat Evren; Lesnes, Elisabeth; Jones, Andrew; Alpago, Hasan; Çetin, Seda; Güler, Abdurrahim; Esperante, Raúl; Patterson, Ross; Abbaszadeh, Mohammad; Moskala, Jiří (2024)
-